MiR-876-3p regulates glucose homeostasis and insulin sensitivity by targeting adiponectin. Issue 1 (October 2018) - Rajan, Sujith; Panzade, Ganesh; Srivastava, Ankita; Shankar, Kripa; Pandey, Rajesh; Kumar, Durgesh; Gupta, Sanchita; Gupta, Abhishek; Varshney, Salil; Beg, Muheeb; Mishra, Raj Kumar; Shankar, Ravi; et al.
Abstract : miRNA has been known to regulate diverse cellular and molecular functions. In the earlier study, we have reported that adipocytes differentiated from human mesenchymal stem cells (hMSC) on 72-h chronic insulin (CI) treatment exhibit insulin resistance (IR). Present study has further explored above model to investigate the role of early expressed miRNAs within human adipocytes to modulate differential adipokine expression as observed during IR. Our results highlight that miR-876-3p regulate glucose homeostasis and its dysregulation leads to IR. We found that miR-876-3p level is a critical determinant of adiponectin expression by virtue of its target within adiponectin 3′UTR. Regulatory effect of miR-876-3p impacts crosstalk between adiponectin and insulin signaling. Rosiglitazone treatment in CI-induced IR adipocytes drastically reduced miR-876-3p expression and increased adiponectin level. In line with this, lentiviral-mediated inhibition of miR-876-3p expression ameliorated CI and high-fat diet (HFD)-induced IR in adipocytes differentiated from hMSC and C57BL/6 mice, respectively. Our findings thus suggest that modulating miR-876-3p expression could provide novel opportunities for therapeutic intervention of obesity-associated metabolic syndrome.